Komunikasi Antarpribadi Masyarakat Beda Agama di Surakarta: Perspektif Interaksionisme Simbolik - Sihabuddin, Sihabuddin; Supriyadi, Agus; Widiyowati, Estu (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2021)
This study aims to analyse the interpersonal communication within multi-religious society in Gendingan village, Surakarta. Using a descriptive qualitative method and symbolic interactionalism approach, the findings indicate that a harmony produced by interpersonal communication amongst Gendingan society is a reflection of one's obedience to the religion and the result of the understanding to his/her religious. In addition, based on symbolic interaction perspective, it is found that, first, the communicator's response to communicants within multi-faith society affected by the environment. Second, the tolerance is allowed but it has remained limited, regardless reducing the meaning of tolerance. Third, there are changes of religious symbolic meaning that affect interpersonal communication actions within multi-religious communities.